Analysis of the Effect of Competence on Employee Performance with Job Satisfaction as an intervening variable - The, Hery Verianto (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aimed to examine and assess the impact of competence on performance in the workplace using job satisfaction as an intermediary variable. The research approach used is a quantitative descriptive causal one. Using the slovin formula on a population of 131, a total of 57 employees were used for the sample. Prior to doing path analysis, validity, reliability, and traditional assumptions were tested using SPSS Version 22, and the Sobel Test was employed for testing mediation. The research found that competence significantly and positively affected employee performance, job satisfaction significantly and positively affected competence, and job satisfaction mediated the effect of competence on performance.